Rancang Bangun Web App Siaga Covid Dengan Metode Haversine - Deo Marvin Yahya; Julianto Lemantara; Dewiyani Sunarto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
The COVID-19 pandemic has hit Indonesia since 2020. The need for emergency treatment is increasingly difficult to obtain when there is a spike in cases. The needs are COVID medicine, oxygen, blood plasma, hospital/isolation site/health center, and ambulance. A lot of time was wasted when looking at the needs from one place to another, this makes people confused about finding their needs. Even though this need must be met immediately because it is related to a person's life and some information systems already exist, such as SIRANAP and FarmaPlus, however, the system for handling COVID-19 is still not integrated and incomplete. Utilization of information system could overcome this problem by processing existing and integrated data, of course, a web-based application (Web App) could be developed that could accommodate the necessary information,The application named Siaga Covid. SiagaCovid was equipped with the Haversine method, Haversine method could be used to find the distance between points, and determine the closest distance where they could get the emergency COVID-19 treatment they need. From the design and development of SiagaCovid, the results obtained from this research were the Haversine method could determine the distance between user and service providers and sorted by the closest distance to the user with high accuracy that could help the community get COVID emergency needs quickly in the application, they could get information about the availability of products and services, or about information of the service itself.